Studies on Effect of pH, Temperature & Light on Protease Production in Leguminous seeds. - Bajgire , Ram Sopanrao (Plantae Scientia, 2020)
Leguminous seeds are one of the important dilatory food of human being. It is the major cultivated food crop in Maharashtra and India. Ten species were isolated from ten different seeds of Legume, out of these Fusarium species only three Fusarium species were tested for the study of the effect of PH, Temperature and Light on Protease Production. The results show that the pH 5.5 and 6.5 is more favourable for Protease activity in F. moniliforme and F. oxysporium. Whereas, F. roseum shows poor activity for Protease Production. The Performance of Temperature on Protease Production was found to be very good at 20c in tested Fusarium species and for Light, the Continuous light showed strong support in F. moniliforme, F. oxysporum and F. roseum. The detail results are shown in the paper.